DEVELOPMENT OF VISUAL ACTIVITY OF STUDENTS WITH HEARING IMPAIRMENTS - Maxmudova Madinaxon Sobirxonovna; Kamolova Xurshida Shamshidin qizi (Bright Mind Publishing, 2025)
This work covers the theoretical and practical aspects of developing visual activity of students with hearing impairments. The study analyzed the psychophysiological characteristics of this category of children, the predominance of visual perception, the influence of visual arts on their cognitive processes and emotional development.
Keywords: Students with hearing impairments, visual activity, special pedagogy, visual perception, demonstration method, creative development, aesthetic education, fine motor skills.